#TITLE_ALTERNATIVE# - SULASTRI (NIM : 90211303) ; Pembimbing Dr. Siti Nurul Khotimah, ELIS
The convenience we get from the simple machine is defined as Mechanical Advantage (MA). Pulley is one example of a simple machine that we often encounter in everyday life. One of the conveniences we get from the pulley is the force that we spend (force power) to lift the load is smaller than than the weight of the load. The mechanical advantage of the pulley can be determined in two way, first to calculate the weight ratio toward the power of the force (static method) and to calculate the ratio of the amount of displacement power toward the amount of displacement load (dynamic method). So far, in junior high school curriculum, determining MA of the pulley is usually determined by calculating the number of rope segments which hold the load upward. However, the tilt angle of force power is not taken into account as one of the factor.